Evaluation of waist circumference to predict general obesity and arterial hypertension in women in Greater Metropolitan Belo Horizonte, Brazil Avaliação da capacidade preditiva da circunferência da cintura para obesidade global e hipertensão arterial em mulheres residentes na Região Metropolitana de Belo Horizonte, Brasil - Gustavo Velásquez-Meléndez; Gilberto Kac; Joaquim Gonçalves Valente; Roberta Tavares; Cibele Queiroz da Silva; Emerson Silami Garcia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
This study examined the capacity of waist circumference (WC) to identify subjects with overweight (BMI ³25) and obesity (BMI ³30), in agreement with internationally recommended levels of action. Data were obtained from 791 women, 15-59 years old. After identifying overweight and obesity according to WC values, sensitivity and specificity were calculated to verify whether WC could be a good risk predictor for hypertension. Associations were tested by linear regression and logistic regression, controlling for confounding. WC cut-off points of 80cm and 88cm correctly identified 89.8% and 88.5% of women with overweight and obesity, respectively. Abdominal obesity (WC ³88cm) was statistically associated with hypertension in the multivariate analysis (OR = 2.88; 95% CI: 1.77-4.67). Hypertension was identified with a sensitivity of 63.8% and 42.8%, and with a specificity of 68.0% and 83.3%, for WC ³80 and ³88, respectively. The proposed cut-off points for abdominal obesity can potentially distinguish individuals at risk for future obesity, but has only moderate power to predict individuals with high blood pressure. Avaliou-se a capacidade que a Circunferência da Cintura (CC) tem em identificar valores de IMC ³25 (sobrepeso) e ³30 (obesidade) a partir de níveis de ação recomendados internacionalmente. Setecentas e noventa e uma mulheres entre 15-59 anos foram recrutadas. Foram calculadas a sensibilidade e a especificidade no diagnóstico de sobrepeso e obesidade e a sensibilidade e especificidade na predição da hipertensão, a partir de valores de CC. As associações foram testadas por análise de regressão linear e regressão logística controlando para o efeito de fatores de confusão. A CC ³80 e ³88cm discriminou corretamente 89,8% de mulheres com IMC ³25 e 88,5% com IMC ³30. A obesidade abdominal (CC ³88cm) esteve associada significativamente com a hipertensão na análise multivariada (OR = 2,88, IC 95%: 1,77-4,67). A hipertensão foi identificada com sensibilidade de 63,8 e 42,8% e especificidade de 68,0 e 83,3% para CC ³80 e ³88, respectivamente. A obesidade abdominal nos pontos de corte propostos pode discriminar adequadamente indivíduos em risco de se tornarem obesos, no entanto, apresenta um poder apenas moderado para discriminar indivíduos com níveis pressóricos altos.